IDENTIFICATION OF FACTORS CONTRIBUTING TO STUDENTS’ DIFFICULTIES IN SOLVING CONTEXTUAL PROBLEMS ON CIRCLE TOPICS USING THE FISHBONE DIAGRAM METHOD - Kowi, Mohamad Saiful; Dewi, Irmawati Liliana Kusuma (Universitas Tanjungpura, 2026)
Mathematical problem solving ability is an important skill for students to face real-world challenges. One material that is closely related to everyday life is circles. However, in practice, many learners have difficulty linking the concept of circles with contextual situations, resulting in their low problem-solving ability. This gap shows the importance of in-depth analysis of the factors that cause these difficulties. This study aims to systematically identify the factors that cause students